Conflict Resolution in Human Rights Cases: The Role of the Supreme Court of Canada - Miriam Cohen; Sarah-Michèle Vincent-Wright (The Constitutional Court of the Republic of Indonesia, 2022)
This paper examines the role of the Supreme Court of Canada (SCC) in resolving human rights conflicts and balancing individual and collective rights. With a multiple control mission, the Court must interpret the Constitution and resolve disputes over competing rights and interests, based on the principle of constitutional democracy. This paper specifically focuses on the SCC’s role in conflict resolution in human rights cases, especially in the complex legal framework of protection existing in Canada. It also addresses how the Court’s rulings may affect the protection of fundamental rights under the Canadian Charter, illustrated by some key examples from the Court’s caselaw. To this end, the first part provides a descriptive overview of the complex fabric of human rights protection in the Canadian constitutional framework. The second part discusses the SCC’s role in protecting human rights within the Canadian legal system. Ultimately, this paper underscores the fundamental role of a Supreme Court in protecting human rights in situations of multiple rights conflicts.